Two-stage anaerobic codigestion of crude glycerol and micro-algal biomass for biohydrogen and methane production by anaerobic sludge consortium - Sureewan Sittijunda (2022)
Optimization of factors affecting biohydrogen production from the codigestion of crude glycerol and microalgal biomass by anaerobic sludge consortium was conducted. The experiments were designed by a response surface methodology with central composite design. The factors affecting the production of hydrogen were the concentrations of crude glycerol, microalgal biomass, and inoculum. The maximum hydrogen production (655.1 mL-H2 /L) was achieved with 13.83 g/L crude glycerol, 23.1 g-VS/L microalgal biomass, and 10.3% (v/v) inoculum. The hydrogenic effluents obtained under low, high, and optimal conditions were further used as substrates for methane production. Methane production rates and methane yield of 868.7 mL-CH4 /L and 2.95 mL-CH4 /L-h were attained with the effluent produced under optimum conditions. The use of crude glycerol and microalgal biomass as cosubstrates had an antagonistic effect on biohydrogen production and a synergistic effect on methane fermentation. The two-stage process provided a more attractive solution, with a total energy of 1.27 kJ/g-VSadded, than the one-stage process.